Social Media in der Arbeitswelt Herausforderungen für Beschäftigte und Mitbestimmung - Carstensen, Tanja (Forschung aus der Hans-Böckler-Stiftung, 2016)
»Enterprise 2.0«: how are working conditions, demands and employee consultation changing through the use of social media within businesses?